Pagans and Christians: fifty years of anxiety - Morgan, T (Oxford University Press, 2019)
This chapter studies E.R. Dodds’s lectures published in 1965 as Pagan and Christian in an Age of Anxiety, which marked a pivotal moment in the modern study of late antiquity. By 1963, Dodds had a long history of combining his scholarly and other interests to create new fields of study. Pagan and Christian draws both on his non-academic interests and on his past research into Neoplatonism, Greek literature, Greek religion, and the ‘irrational’, encompassing the supernormal or paranormal in antiquity. Dodds argued for seeing common ground between pagan and Christian mentalities in a way which can now be taken for granted but was anything but typical at the time. In the process, he created a new field of study and, if not many scholars have followed him in studying the whole breadth of the field, there has been much more serious discussion since of many of its elements.